Angiographic dynamics of coronary flow state after percutaneous coronary intervention in carriers of polymorphic RS1800470 variants of the TGF-β1 gene - D. A. Brusentsov; S. Yu. Nikulina; P. A. Shesternya (Российский кардиологический журнал)
Aim. To study the relationship between the angiographic dynamics of the state of the coronary bed in patients undergoing percutaneous coronary intervention (PCI) due to myocardial infarction (MI) and the carriage of polymorphic rs1800470 variants of the transforming growth factor beta-1 gene (TGF-β1).Material and methods. The study included 89 men with MI of the Caucasian race aged 32 to 65 years (52 [45,0-58,0]). Genomic deoxyribonucleic acid (DNA) was extracted from venous blood by phenol-chloroform technique. The rs1800470 polymorphism of the TGF-β1 gene was tested using real-time polymerase chain reaction (PCR) (TaqMan probes, AB 7900HT). Assessment of the severity of coronary lesions was carried out initially according to the standard coronary angiography (CAG) protocol with the calculation of the Gensini score. CAG was also conducted in the dynamics after 5-103 months (42,3±29,5 months) of the study beginning.Results. In male carriers of the rs1800470 A allele of the TGF-β1 gene, the mean values of the Gensini score statistically significantly increased (47,5±34,1 (CAG-1) and 64,5±35,5 (CAG-2), p <0,001) in comparison with carriers of the homozygous GG rs1800470 variant of the TGF-β1 gene (43,5±21,1 (CAG-1) and 46,2±23,2 (CAG2), p=0,066). In patients who had rs1800470 A allele of the TGF-β1 gene, a 20%decrease in the Gensini score was observed after 7 months (p=0,013), and 30% — after 5 months (p=0,003) of the initial CAG. The development of late stent restenoses in carriers of the rs1800470 A allele and the homozygous risk genotype AA of the TGF-β1 gene was noted at an earlier date — 8 (p=0,047) and 12 months (p=0,002), respectively.Conclusion. Currently, the conduct of CAG in dynamics in patients undergoing PCI is recommended as clinically indicated. The exception is the group of patients who underwent endoprosthesis replacement of the left coronary artery or have uncorrected stenosis of a different location from 3 to 12 months after PCI. The presented data show a possible predictor role of rG1800470 polymorphism of the TGF-β1 gene in relation to the progression of coronary atherosclerosis and the development of late stent restenoses.